(untitled) (Inženierzinātņu un augstskolu vēsture, 2018)
Ekonomists Vladimirs Kosinskis (1864–1938) dzimis tagadējās Ukrainas teritorijā. Viņš Maskavas Universitātē absolvēja divas fakultātes: Fizikas-matemātikas (1887) un Juridisko (1891). Viņš ir pazīstamā krievu ekonomista, statistiķa Aleksandra Čuprova skolnieks un strādājis Maskavas Universitātē, Rīgas Politehniskajā un Kijevas Politehniskajā institūtā, Odesas Universitātē, Prāgas Krievu universitātē un Latvijas Universitātē, kur profesors zinātniskajam darbam sagatavoja A. Zaļo, K. Zīvertu, J. Vītolu, A. Aizsilbnieku. Vladimirs Kosinskis ieguva autoritāti kā speciālists tautsaimniecības teorijā. Vairums viņa darbu publicēti krievu valodā, latviski – viņa lekcijas. Profesors miris 1938. gadā Rīgā un apbedīts Pokrova kapos. Professor Vladimir Kosinski’s (1864–1938) Life and Work Professor Vladimir Kosinski (1864–1938) is a well-known statistician and economist. He was born in a noble family in the province of Chernigov. After graduating from the Gymnasium, he entered the University in Moscow where he was a student at two faculties: the Faculty of Physics and Mathematics (1887) and Faculty of Law (1891). He studied also abroad. In 1900, Vladimir Kosinski was appointed a privatdocent at Moscow University; from 1901 to 1904, he was an Adjunct Professor with the Riga Polytechnic Institute and from 1904 to 1909 – an Extraordinary Professor of the Odessa Polytechnic Institute. In 1907, he defended his Thesis at Moscow University and received the scientific degree of Doctor of Economics and Statistics. From 1909 to 1919, he was a Professor with the Kyiv University of St. Vladimir; from 1922 to 1928 – a Professor with the Russian Law Faculty in Prague (Czechoslovakia); from 1928 to 1938 ‒ a Professor with the Department of Economy and Law of the University of Latvia. From 1936, he was a freelance professor. He died in 1938 in Riga, Latvia. During his long career of professorship, Kosinski prepared many brilliant specialists, among them the well-known Latvian scientist Arnolds Aizsilnieks (1898–1982), and is the author of numerous scientific works. Keywords: Vladimir Kosinski, Riga Polytechnic Institute, University of Latvia, economics. Жизнь и деятельность профессора Владимира Косинского (1864–1938) Экономист, специалист в области политэкономии В. Косинский родился на территории нынешней Украины. В Московском университете он окончил два факультета: отделение математических наук Физико-математического факультета (1887) и Юридический факультет (1891). Он был учеником известного русского экономиста, статистика Александра Чупрова и работал в Московском университете (1900–1901), в Рижском пол